ADAPTASI BENTUK BANGUNAN PUSAT PEMBERDAYAAN EKONOMI PEREMPUAN DI BEKASI TERHADAP KONDISI LAHAN - Sakinah Ruhi Sya'bania; Lily Mauliani; Yeptadian Sari (PURWARUPA Jurnal Arsitektur, 2019)
ABSTRACT. ‘Aisyiyah Center is a Women's Creativity Center at Bekasi City aims to accomodate all the main activities of the 'Aisyiyah Headquarters which is an organization of women within Persyarikatan Muhammadiyah in carrying out the endeavor of encouraging good and discouraging evil in all fields of life based on Qurán and Hadith. This main activity is supported by social business activities as the Women's Creativity Center in social economics, integrating the functions of social buildings and commercial buildings with 'Aisyiyah characters in a modern architectural design. Through a modern architectural design approach that is integrated by the characters of 'Aisyiyah, it becomes a step to make it happen, besides 'Aisyiyah Center as a social building of 'Aisyiyah Organization which is combined with commercial buildings must have an appeal to the general public, even to those who are not very familiar with 'Aisyiyah, thus the processing of the form of mass and facade became an important thing in the planning and design of 'Aisyiyah Center. The business in this 'Aisyiyah Center is a center for UMKM (Micro, Small, and Medium Enterprises) activities. 'Aisyiyah Center facilitates activities ranging from training, production, marketing to connecting directly with consumers; for this reason, market place facilities and other meeting facilities as well as wedding activities, both indoor and outdoor, are equipped with accommodation as an effort from 'Aisyiyah Center to directly connect economic actors with consumers.Keywords : ‘Aisyiyah, Charity Business, Creativity, Women's, Center.